EVALUASI KEBIJAKAN BEASISWA BIDIK MISI DI UNIVERSITAS RIAU TAHUN 2010-2014 - Risno H. Pardede; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Bidik Misi scholarship is a programm to all students in College especially to all least coast fee about study and appreciate to the best student at Campus. Indonesia has 148 campus to the receive the Bidik Misi scholarship. University of Riau is a one of a campus get the Bidik Misi 2010 until 2014 scholarship and program has continue to the least poor in this area. Many problems who the writer found the some unjustice about the Bidik Misi scholarship in University of Riau. The writer has information from rektorat building in University of Riau. After that, the writer check this data, and begin to analizy with theory. The writer of this research using William Dunn theory about Evaluation of Policy. This is a theory to all problems, so the writer get a solution in this research after the writer finish interview about Bidik Misi scholarship.Keywords : Bidik Misi scholarship, Evaluation of Policy, University of Riau